The acceptance of Capability Maturity Model Integration (CMMI) in Motorola Malaysia Sdn. Bhd. : a Case Study / Mohd Hasnur Asim @ Hashim - Asim @ Hashim, Mohd Hasnur (2005)
Nowadays, there are various types of maturity models, standards, methodologies, and guidelines that can help an organization improve the way it does business, and one of the best maturity models that world wide organizations implement is CMMI. The CMMI, like its predecessor (CMM), describes five distinct levels of maturity; level 1 (Initial), level 2 (managed), level 3 (defined), level 4 (quantitatively managed) and level 5 (optimized). Although many organizations found these models to be useful, they also struggled with problems caused by overlap, inconsistencies and to minimize the gap between CMM and CMMI. Because of the implementation of this model are really new in Malaysia, this research aims to assess how the acceptance of CMMI in Motorola Malaysia Sdn. Bhd., identify the advantages and problem encountered in the transitions from CMM to CMMI. The evaluation is based on the Technology Acceptance Model (TAM) with two particular beliefs, perceived usefuhiess and perceive ease of use. Approximately 100 of questionnaires were distributed to all staff in GSG Malaysia to get their opinion regarding to this research. From the results, the advantages of CMMI were obtained and problems during the transitions from previously model to CMMI in Motorola Malaysia Sdn. Bhd. were identified.